A Systematic Review and Meta-analysis of Techniques for Management of Postoperative Lymphatic Leaks After Groin Surgery. Issue 2 (28th August 2022) - Song, Siyou; Parmeshwar, Nisha; Steiner, Gabriela; Kim, Esther A.
Abstract : Purpose: Plastic surgeons are often consulted to manage postoperative groin lymphatic leaks that may lead to serious sequelae if not promptly treated. Because there are no standardized guidelines for best treatment practices, this systematic review and meta-analysis evaluates the outcomes of multiple management modalities to ultimately guide decision making for surgeons. Methods: Literature surrounding lymphatic leaks in the groin was reviewed from PubMED, MEDLINE, EMBASE, and the Cochrane Library from January 1, 2000, to December 1, 2020 according to Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. The inciting procedure, postoperative lymphatic complication, used management, and days to resolution were recorded. Pairwise comparisons using the Wilcoxon rank sum test with Bonferroni continuity correction were used to determine which treatment modalities differed significantly and accounted for multiple hypothesis testing. Results: A total of 1468 total studies were initially found, which narrowed to 267 unique articles after duplicates were removed. Twelve articles ultimately met the inclusion criteria and were included in the data analysis. There were 264 groin complications, of which 217 were initially treated with conservative management, 81 with a minimally invasive procedure, and 125 with surgery. More than 95% of all cases had an inciting procedure of a vascular nature. For vascular surgery–induced lymphatic leak treated by minimally invasive and surgical techniques, a significantly higher number of cases resolved compared with those treated conservatively (100% and 96.7% compared with 29.5%, respectively, P < 0.05). However, there were no significant differences in the proportion that resolved between the minimally invasive and surgical cases ( P = 0.11). Vascular cases that were only managed with surgery had significantly shorter days to resolution compared with cases that first attempted conservative management ( P < 0.001). Conclusions: Both minimally invasive and surgical options have increased odds of resolution and lower failure rates compared with conservative management alone. The odds of resolution were higher when treated with more invasive procedures compared with conservative-only management, but the mean days to resolution was longer. This meta-analysis depicts successful resolution with procedural management and supports an initial trial of minimally invasive techniques.